Bendamustine–rituximab elicits dual tumoricidal and immunomodulatory responses via cGAS–STING activation in diffuse large B-cell lymphoma - Enguang Bi; Yang Zhou; Wei Lin; Ling Jiang; Jie Ren; Wei Meng; Wenli Zhao; Ruipei Xiao; Yudian Xiao (Journal for ImmunoTherapy of Cancer)
Background Bendamustine–rituximab (BR) therapy stands out as a promising alternative for elderly patients with diffuse large B-cell lymphoma (DLBCL), demonstrating notable efficacy when conventional regimens pose challenges. Despite its clinical success, the intricate mechanisms underlying BR therapy have remained elusive.Methods DLBCL cell lines were used to investigate the mechanism of BR therapy in vitro. RNA-seq and Western blot were used to explore the target pathways of BR therapy. STING was knocked out using Crispr-cas9 and inhibited using H-151 to investigate its role in BR therapy. Bulk RNA-seq and single-cell RNA-seq data from patients were analyzed to investigate the association between STING and pyroptosis pathways, validated using STING downregulated cells. Flow cytometry, transwell experiments and co-culture experiments were performed to investigate the inflammatory phenotype of DLBCL cells after BR treatment and its effect on T-cell recruitment and activation.Results This study elucidates that BR elicits direct tumoricidal effects by promoting apoptosis and inducing cell cycle arrest. The synergistic impact with rituximab is further potentiated by complement addition, demonstrating the pivotal role of in vivo antibody-dependent cellular cytotoxicity. Moreover, our investigation reveals that, through a cGAS–STING-dependent pathway, prolonged exposure to BR induces pyroptosis in DLBCL cells. Activation of the cGAS–STING pathway by BR therapy triggers the release of inflammatory factors and upregulates major histocompatibility complex molecules, shaping an immunologically hot tumor microenvironment.Conclusions This unique dual influence not only directly targets DLBCL cells but also engages the patient’s immune system, paving the way for innovative combination therapies. The study provides comprehensive insights into the multifaceted actions of BR in DLBCL, offering a foundation for refined and personalized treatment strategies in elderly patients.